1984
DOI: 10.1177/0148607184008005560
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Complications from Insertion of Subclavian Venous Feeding Catheters: Comparison of de Novo Percutaneous Venipuncture to Change of Catheter Over Guidewire

Abstract: Since a percutaneous catheter insertion into the subclavian vein can be tedious, time consuming, and risky, we have compared the morbidity of 137 de novo subclavian catheter insertions to that of 93 reinsertions over guidewire. Mechanical complications were significantly higher (p less than 0.03) in those with catheter insertions (8.8%) than in those with the guidewire insertions (2.2%). These included pneumothorax (4), arterial puncture (4), catheter-size bleed (3), and hemothorax (1) in the catheter insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Most studies examined by HICPAC concluded that, in cases where the catheter being removed is known to be infected, guidewire exchange is contraindicated. 302,[304][305][306][307] A systematic review concluded that, compared with new site replacement, guidewire exchange was associated with a trend toward a higher rate of subsequent catheter colonisation, regardless of whether patients had a suspected infection at the time of replacement. Guidewire exchange was also associated with trends toward a higher rate of catheter exit-site infection and CR-BSI.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies examined by HICPAC concluded that, in cases where the catheter being removed is known to be infected, guidewire exchange is contraindicated. 302,[304][305][306][307] A systematic review concluded that, compared with new site replacement, guidewire exchange was associated with a trend toward a higher rate of subsequent catheter colonisation, regardless of whether patients had a suspected infection at the time of replacement. Guidewire exchange was also associated with trends toward a higher rate of catheter exit-site infection and CR-BSI.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretically, a new CVC insertion at a new site exposes the patient to some risk of arterial or lung puncture while, logically, GWX will eliminate the risk associated with such a puncture [16-19]. However, GWX may expose patients to a greater risk of line contamination through inadequate protection of the insertion field with anti-bacterial solutions.…”
Section: Introductionmentioning
confidence: 99%
“…A widely practiced technique intended to reduce the incidence of mechanical complications associated with central venous catheterization is the use of Seldinger guide wire exchanges in lieu of routine catheter replacement at a new site. 16,[23][24][25]39,45,49,56,69,70,[110][111][112] This allows a new catheter to be substituted with substantially less risk of insertion-related complications. However, the new catheter is inserted over a guide-wire that might have been contaminated during the removal of the previous catheter.…”
Section: Prevention Of Catheter-associated Infectionmentioning
confidence: 99%